Ventricular myosin light chain 1 is developmentally regulated and does not change in hypertension. - McNally, E M (1989)
Cardiac myosin heavy chain (MHC) isoform distribution has been shown to undergo changes during development, in response to hormonal stimuli, and during pathologic states like hypertension. We initiated a study of myosin light chain 1 (MLC1) expression in cardiac tissue to determine whether MLC1 undergoes changes similar to those seen for MHC. We isolated a full length cDNA for the predominant MLC1 sequence in rat hearts. This gene is expressed in ventricular tissue at much higher levels than in atrial tissue. Based on its expression pattern and sequence homology, this cDNA encodes the rat ventricular MLC1 and has been named RVMLC1. RVMLC1 is expressed at very low levels in cardiac tissue during early development and is expressed abundantly after birth and in adult hearts. The expression of RVMLC1 was found not to change in the hearts of rats with renovascular hypertension.